Praying and Preying : Christianity in Indigenous Amazonia - Vilaça, Aparecida, 1958- (Anthropology of Christianity, 2016)
Praying and Preying offers one of the rare anthropological monographs on the Christian experience of contemporary Amazonian indigenous peoples, based on an ethnographic study of the relationship between the Wari', inhabitants of Brazilian Amazonia, and the Evangelical missionaries of the New Tribes Mission. Vilaça turns to a vast range of historical, ethnographic and mythological material related to both the Wari' and missionaries perspectives and the author's own ethnographic field notes from her more than 30-year involvement with the Wari' community. Developing a close dialogue between the Melanesian literature, which informs much of the recent work in the Anthropology of Christianity, and the concepts and theories deriving from Amazonian ethnology, in particular the notions of openness to the other, unstable dualism and perspectivism, the author provides a fine-grained analysis of the equivocations and paradoxes that underlie the translation processes performed by the different agents involved and their implications for the transformation of the native notion of personhood.